2022
DOI: 10.1002/chem.202104328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Asx Turn Types and Their Connate Relationship with β‐Turns

Abstract: Models of asparagine‐containing dipeptides specifically designed to favor intrinsic folding into an Asx turn were characterized both theoretically, by using quantum chemistry, and experimentally, by using laser spectroscopy in the gas phase. Both approaches provided evidence for the spontaneous folding of both the Asn‐Ala and Asn‐Gly dipeptide models into the most stable Asx turn, a conformation stabilized by a C10 H‐bond that was very similar to a type II’ β‐turn. In parallel, analysis of Asx turns implicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…On the contrary, a study of a database of 500 proteins found that the frequency of occurrence of Asx turn is type-Ⅱ′, while the most common type is βI turn 30 . These findiA recent study of Asx also supported these findingsn-Ala and Asn-Gly in crystallized protein structures in the PDB 31 , revealing that the most common Asx turn in these two sequences are type-Ⅱ′ and type-Ⅱ, respectively. In sum, our results suggest that azaAsn and azaAsp residues in models 4 and 5 could have different folding patterns than natural peptides and the,y could also enhance the formation of a type-Ⅰ Asx turn instead of type-Ⅱ′ mostly found in peptides.…”
Section: Asx Turn Vs βⅰ-Tun In Ac-azaasx-pro-nhme (X= N or P)supporting
confidence: 66%
See 1 more Smart Citation
“…On the contrary, a study of a database of 500 proteins found that the frequency of occurrence of Asx turn is type-Ⅱ′, while the most common type is βI turn 30 . These findiA recent study of Asx also supported these findingsn-Ala and Asn-Gly in crystallized protein structures in the PDB 31 , revealing that the most common Asx turn in these two sequences are type-Ⅱ′ and type-Ⅱ, respectively. In sum, our results suggest that azaAsn and azaAsp residues in models 4 and 5 could have different folding patterns than natural peptides and the,y could also enhance the formation of a type-Ⅰ Asx turn instead of type-Ⅱ′ mostly found in peptides.…”
Section: Asx Turn Vs βⅰ-Tun In Ac-azaasx-pro-nhme (X= N or P)supporting
confidence: 66%
“…Since Asx turns are mimicry of β turns, the dihedral angles ϕe and ψe of Asx turn (Fig. 6) should resemble those of i+1 in β turns, while ϕ and ψ of residue i+1 of Asx turns should resemble those of residue i+2 in β turns 30,31 . -80 0 Furthermore, the azaAsx-Pro chain contains another C10 pseudo-cycle similar to an Asx turn, which is related to the H.B.…”
Section: Asx Turn Vs βⅰ-Tun In Ac-azaasx-pro-nhme (X= N or P)mentioning
confidence: 99%
“…However, in SseK2/NleB2 effectors, we found that the first aspartate in the DxD motif was previously intertwined with the C10 H-bond network, namely the Asx-turn (Asp/Asn-turn), which is incapable of binding Mn 2+ . Recently, Asn-containing peptide models, specifically designed to not form the β-turn, favor intrinsic folding into an Asx-turn; analysis of Asn turns in PDB proteins confirmed that the Asx-turn is the most stable innate structure before the backbone β-turn 24 . This suggests that the catalytic aspartate side-chain of the SseK2/NleB2 DxD motif caged-in Asx-turn is more tightly intertwined than the free aspartate side-chain of the fatal SseK1/3 and NleB1 DxD motifs in the backbone Type-I-turn, which prohibits the catalytic DxD motif from binding Mn 2+ and glycosylating targets.…”
Section: Introductionmentioning
confidence: 99%
“…6 Nevertheless, recent in silico research has shown that Asx−Gly sequence in a small dipeptide model is able to induce type II′ β-turns independently. 7 Since an effective approach to stabilize turn conformation is the synthesis of rigid peptide turn surrogates, we present herein the design, synthesis, and conformational analysis of novel hydantoin-based loops, where (1) the structure of Asn is embedded into a more rigid hydantoin five-membered ring, and (2) a flexible glycine or an even more flexible ethylenediamino residue is tethered to the Nα of Asn (or N1 of the hydantoin ring), respectively, in Hyd-loop I and Hyd-loop II (Figure 1, bottom). We reasoned that if a turn structure can exist in a flexible Asp−Gly sequence, even if triggered by a pre-existing β-turn, the designed hydantoin loops could possibly induce in itself a defined turn conformation with a 9-membered ring intramolecular Hbond.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, the debate on which turn pre-exists, thus fostering the formation of the second, is still open . Nevertheless, recent in silico research has shown that Asx–Gly sequence in a small dipeptide model is able to induce type II′ β-turns independently . Since an effective approach to stabilize turn conformation is the synthesis of rigid peptide turn surrogates, we present herein the design, synthesis, and conformational analysis of novel hydantoin-based loops, where (1) the structure of Asn is embedded into a more rigid hydantoin five-membered ring, and (2) a flexible glycine or an even more flexible ethylenediamino residue is tethered to the Nα of Asn (or N1 of the hydantoin ring), respectively, in Hyd-loop I and Hyd-loop II (Figure , bottom).…”
Section: Introductionmentioning
confidence: 99%